Analysis of mutual capacitance and inductance of printed circuit - V.G. Ivanov (National Technical University "Kharkiv Polytechnic Institute", 2014)
The article analyzes the mutual capacitance and inductance of printed circuit and introduces an evaluation technique for conductor-to-conductor capacitance under electrical connections tracing, the technique based on a multi-layer channel model.